Data Sources Integrator for Management by Indicators - Illescas, Gustavo (2018)
This current work exposes the research and development of a tool for the integration of data sources in the context of management by indicators. The main benefits of this research are the administrators of databases that will work with a powerful tool that will allow them to effectively manage the updating of indicators previously defined by information managers. These information managers are the most interested in that the indicators are updated in the databases for the taking of decisions which will directly benefit them. This work gives rise to a thesis in Systems Engineering and the result could be applied in the TIC direction of the Faculty of Exact Sciences as it is expressed in the case study, taking part of the Strategic Plan of Engineers Formation promoted by the Secretary of University Policies.